KEBIJAKAN PEMERINTAH TENTANG PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI PASAR TRADISIONAL KOTA BANJARMASIN - Normajatun Normajatun; Abdul Haliq (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2020)
This research is aimed to know the description of the implementation of the policy on the reduction of the use of plastic bags at traditional markets in Banjarmasin. Research was conducted by using qualitative method and descriptive analysis. From the results of this research, when viewed from the factor of communication, the implementation of Government policy on the reduction of the use of plastic bags for the traditional market is done through socialization, and have clarity and are consistent. Of factor resources, the implementation of the policy of this government as the executive is the Department of the Environment that is in synergy with all SKPD, for the budget source of the budget data and the means provided by the Government of the City. Of factors of disposition, policy implementers already have a commitment to have democratic attitudes. Of the factor structure of the bureaucracy, the socialization policy of the government has been guided by the SOP.. Obstacles encountered in the implementation of this policy, namely in terms of the still low public response to the Government appeal and the lack of understanding of the community.against the division of bakul purun carried out by the Government.